Psychosocial and maternal care needs of recently delivered women during the postpartum period - Mustafa Kilavuz; Seçil Topaloğlu (BMC Pregnancy and Childbirth)
Abstract This qualitative study was conducted at a family health center in Istanbul, Turkey, and aimed to explore the psychosocial and maternal care needs and emotional experiences of women during the first six weeks postpartum. Women who could understand the local language were included in the study. Among the participants, 80% were local Turkish women and 20% were migrant women. A total of 10 women were selected through purposive sampling. Descriptive content analysis revealed four main themes: (1) Causes of stress, (2) Expression and interpretation of stress, (3) Sources of support, and (4) Areas of support. The findings highlight the crucial role of social support in addressing the psychosocial needs of postpartum women and promoting maternal and newborn well-being.